Dynamics of spinal cord compression with different patterns of thoracolumbar burst fractures: Numerical simulations using finite element modelling. (February 2020) - Diotalevi, Lucien; Bailly, Nicolas; Wagnac, Éric; Mac-Thiong, Jean-Marc; Goulet, Julien; Petit, Yvan
Abstract: Background: In thoracolumbar burst fractures, spinal cord primary injury involves a direct impact and energy transfer from bone fragments to the spinal cord. Unfortunately, imaging studies performed after the injury only depict the residual bone fragments position and pattern of spinal cord compression, with little insight on the dynamics involved during traumas. Knowledge of underlying mechanisms could be helpful in determining the severity of the primary injury, hence the extent of spinal cord damage and associated potential for recovery. Finite element models are often used to study dynamic processes, but have never been used specifically to simulate different severities of thoracolumbar burst fractures. Methods: Previously developed thoracolumbar spine and spinal cord finite element models were used and further validated, and representative vertebral fragments were modelled. A full factorial design was used to investigate the effects of comminution of the superior fragment, presence of an inferior fragment, fragments rotation and velocity, on maximum Von Mises stress and strain, maximum major strain, and pressure in the spinal cord. Findings: Fragment velocity clearly was the most influential factor. Fragments rotation and presence of an inferior fragment increased pressure, but rotation decreased both strains outputs. Although significant for both strains outputs, comminution of the superior fragment isn't estimated to influence outputs. Interpretation: This study is the first, to the authors' knowledge, to examine a detailed spinal cord model impacted in situ by fragments from burst fractures. This numeric model could be used in the future to comprehensively link traumatic events or imaging study characteristics to known spinal cord injuries severity and potential for recovery. Graphical abstract: Unlabelled Image Highlights: A novel numeric model is proposed for the study of spinal cord injuries dynamics. Sixteen scenarios of vertebral fragments retropulsion are replicated. Predictors of increased stress and strain sustained by the spinal cord are proposed. Shear and longitudinal strains may contribute to the spinal cord primary injury.